2012
DOI: 10.1186/1471-2377-12-110
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of essential tremor in urban Lagos, Nigeria: a door-to-door community-based study

Abstract: BackgroundEssential tremor (ET) is one of the commonest movement disorders though the prevalence varies globally. There is paucity of data on ET prevalence in sub-Saharan Africa. The study aimed to determine the prevalence of ET in a Nigerian community.MethodsThis door-to-door survey was conducted in two stages. In Stage 1, 3000 randomly selected residents of an urban centre in Lagos, Nigeria, were screened using a questionnaire to detect symptoms of movement disorder. 234 participants who responded positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Similar to our study, there are few young individuals' tremor prevalence studies compared to older population, and in these studies, the prevalence between the ages 17-39 changes between 0.481%-2.7% [6][7][8][9][10] (Table 2). In a study where Sur et al [7] included also the young individuals, the results were less than our study, while in the study of Küsbeci et al [8] in 221 young individuals (17-26 years of age), the ET prevalence was found similar to ours (3%).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Similar to our study, there are few young individuals' tremor prevalence studies compared to older population, and in these studies, the prevalence between the ages 17-39 changes between 0.481%-2.7% [6][7][8][9][10] (Table 2). In a study where Sur et al [7] included also the young individuals, the results were less than our study, while in the study of Küsbeci et al [8] in 221 young individuals (17-26 years of age), the ET prevalence was found similar to ours (3%).…”
Section: Discussionsupporting
confidence: 54%
“…The physiological tremor (PT) is defined as the postural tremor with low amplitude at classically [8][9][10][11][12] Hz frequency that may be seen in everybody and may increase with anxiety and fatigue [1,11]. Healthy people may show some tremor but this condition does not cause any complaint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[9][10][11][12][13][14] Of these 34 studies, 16 were identified in which: 1) the method of case ascertainment involved either neurological examination of all subjects in a population sample or administration of a screening questionnaire followed by neurological examination, and the sensitivity of the screen was provided, and 2) estimates of prevalence were provided within age strata. 5,6,11,12,14,[16][17][18][19][20][21][22][23][24][25][26] Of these 16, 5,6,11,12,14,[16][17][18][19][20][21][22][23][24][25][26] 12 used diagnostic criteria for ET that are not ideally suited to epidemiological investigations (e.g., the Consensus Statement of the Movement Disorder Society 27 ) because they do not sufficiently separate ET from other entities such as enhanced physiological tremor, and/or used non-neurologists to assign ET diagnoses, which is not optimal. Four studies remained; these were conducted in Israel, 18 Turkey, 5,20 and Spain.…”
Section: Resultsmentioning
confidence: 99%
“…8 The search yielded 34 population-based prevalence studies. 1,[9][10][11][12][13][14] The methodology of each identified study was assessed, and methodologically more rigorous studies were selected for further review. The methodological issues of greatest importance were as follows: 1) all subjects in the sample received an in-person neurological examination or the study provided information to indicate that the sensitivity of the screening questionnaire used during the first phase of case ascertainment was high, 2) neurologists assigned the ET diagnoses, 3) the study used diagnostic criteria that sufficiently separate ET from other entities such as enhanced physiological tremor, which are common in the population, and 4) the study provided separate age-specific estimates of prevalence.…”
Section: Methodsmentioning
confidence: 99%